GAMBARAN HUBUNGAN USIA GESTASI DENGAN KEJADIAN IKTERUS PADA NEONATUS - Vina Elvira Ayu Prastika; Haris Sofyana; Henny Cahyaningsih; Sri Ramdaniati (Jurnal Kesehatan Siliwangi, 2020)
ABSTRACT Xiii, 60 pages, 5 chapters, 1 chart, 4 tables, 1 picture, 3 attachments This research is motivated by effect of neonates from jaundice, that was like brain damage, seizures, and cyanosis. The incidence of jaundice in Indonesia (2016) it was 51.47% and the neonatal mortality rate in Indonesia (2017) is was 19/1000 births. Deaths of neonates could be happen because of kern jaundice. That was bilirubin didn’t conjugate higher, and it called hyperbilirubin. The purpose of research is to describe about correlation between gestational age and jaundice in neonates. The method of research that used analytic with the Systematic Literature Review, that was about identifying all of evidence at a topic of the research. The number of journals used was 6 journals. The results showed the incidence of physiologic jaundice in preterm neonates> 50% and physiological jaundice in mature neonates around 40% while the pathological jaundice incidence in premature neonates was around 50% -90% and pathological jaundice in mature neonates <50%. This study showed a p-value <0.05 there was a significant relationship between gestational age and the incidence of jaundice in neonates. Recommendations for health services are to make preventive efforts to provide health promotion, for educational institutions as a source of reading or literature in child nursing courses, for the profession as a health or counseling activity, and for subsequent researchers as a reference for preliminary data for the development of hyperbilirubin research. Key words: Gestational age, Jaundice, Neonates